Volume change behavior of phosphogypsum treated clayey soils contaminated with inorganic acids – a micro level study - Chavali, Rama Vara Prasad; P, Hari Prasad Reddy (Journal of Environmental Engineering and Landscape Management, 2018)
Soils exhibit undesirable volume changes when exposed to high concentrations of acids, which is manifested most frequently in the beds of foundations of industrial establishments associated with their production or use. However, control of this phenomenon has received less attention than it deserves. This paper aims to investigate the mineralogical and micro-structural changes occurred during the volume change behavior of phosphogypsum treated clayey soils contaminated with sulfuric acid and phosphoric acid solutions. Oedometer test results showed high swelling and low compressibility for acid contaminated soils than that of water. The change in microstructure towards flocculated fabric along with mineralogical transformations are responsible for the volume changes in soils. The mineralogical changes that affected the volume change behavior are discussed with FT-IR, XRD and SEM analysis. Phosphogypsum treatment was found to be effective in controlling volume changes in soils with phosphoric acid, whereas in the case of sulfuric acid found to be futile.